Comparison of cotrimoxazole, ampicillin, and chloramphenicol in treatment of experimental Haemophilus influenzae type B meningitis. - Perfect, J R (1980)
To evaluate cotrimoxazole in the treatment of bacterial meningitis, we compared its action with that of ampicillin and chloramphenicol in experimental Haemophilus influenzae type b meningitis. Both trimethoprim and sulfamethoxazole penetrated well into the cerebrospinal fluid of infected rabbits, reaching 40 and 26%, respectively, of their simultaneous serum levels. Levels measured 30 and 60 min after intravenous injection exceeded the minimum inhibitory concentration of this combination for H. influenzae by 10- to 100-fold. The mean ratio of trimethoprim to sulfamethoxazole in cerebrospinal fluid was 1:22. Cotrimoxazole was as effective as ampicillin in therapy of beta-lactamase-negative H. influenzae meningitis and as effective as chloramphenicol for a beta-lactamase positive strain. These findings corroborate favorable preliminary clinical experience reported by others and indicate that cotrimoxazole deserves further study in the therapy of bacterial meningitis.